2020
DOI: 10.3389/fphar.2020.585680
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA 554 Promotes Cardiac Fibrosis via TGF-β1 Pathway in Mice Following Myocardial Infarction

Abstract: Rationale: Cardiac fibrosis is observed in nearly every form of myocardial disease. Long non-coding RNAs (lncRNAs) have been shown to play an important role in cardiac fibrosis, but the detailed molecular mechanism remains unknown.Object: We aimed at characterizing lncRNA 554 expression in murine cardiac fibroblasts (CFs) after myocardial infarction (MI) to identify CF-enriched lncRNA and investigate its function and contribution to cardiac fibrosis and function.Methods and Results: In this study, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It is the terminal differentiation and nonrenewability of myocardial tissue in adulthood that prevent the heart from proliferating and repairing itself after the heart injuries, such as ischemia reperfusion injury (IRI) and MI [10][11][12][13][14]. The response of the mammalian heart to MI and the concomitant cell death is the substitution of fibroblasts, extracellular matrix reticulum, and proliferating cells for the damaged myocardium, thereby the scar-forming, called ventricular remodeling [46,47]. Extensive cell therapy studies have used embryonic stem cells (ESC) and induced pluripotent stem cells (iPSC) as exogenous sources of new cardiomyocytes for treatment [9,48].…”
Section: Discussionmentioning
confidence: 99%
“…It is the terminal differentiation and nonrenewability of myocardial tissue in adulthood that prevent the heart from proliferating and repairing itself after the heart injuries, such as ischemia reperfusion injury (IRI) and MI [10][11][12][13][14]. The response of the mammalian heart to MI and the concomitant cell death is the substitution of fibroblasts, extracellular matrix reticulum, and proliferating cells for the damaged myocardium, thereby the scar-forming, called ventricular remodeling [46,47]. Extensive cell therapy studies have used embryonic stem cells (ESC) and induced pluripotent stem cells (iPSC) as exogenous sources of new cardiomyocytes for treatment [9,48].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 inhibitor (TEW-7197) could significantly inhibit the fibrosis-promoting function of lncRNA 554 in CFs. These results indicated that the effect of lncRNA 554 on MI-induced myocardial fibrosis was dependent on the TGF-β1 signaling pathway ( Luo et al, 2020 ). Wisper (WISP2 super enhancement factor associated RNA) is a myocardial fibroblast enriched lncRNA that regulates myocardial fibrosis.…”
Section: Lncrnas and Secondary Changes Of MImentioning
confidence: 97%
“…Long non-coding RNAs (lncRNAs) are an emerging class of non-coding RNAs, which are more than 200 nucleotides in length ( Luo et al, 2020 ; Wang et al, 2021b ). lncRNAs can regulate various biological functions at epigenetic, transcriptional and post-transcriptional levels ( Huang, 2018 ) and bind DNA, RNA and protein ( Wang Y.-N. et al, 2021 ).…”
Section: Crosstalk Between Tgf-β1/smad and Long Non-coding Rna In Tub...mentioning
confidence: 99%